An Analysis of the Effectiveness of X-Ray as a Supporting Tool in the Autopsy Process: a Literature Review - Kamijantono, Harry; Azhar, Adang (Newinera Publisher, 2025)
This study aims to analyze the effectiveness of using X-ray technology as a supporting tool in the forensic autopsy process. The method used is qualitative with a literature study approach that includes various scientific sources such as journals, books, and medical documents. The results showed that X-ray plays an important role in modern autopsy, especially as a non-invasive method to detect foreign bodies, fractures, and internal trauma that are not visible to the naked eye. In addition, technological developments such as postmortem CT (PMCT) and virtual autopsy (virtopsy) utilizing X-ray have also further expanded the application of imaging in the autopsy process, providing a three-dimensional view of the body without the need to perform surgery. Literature studies show that X-ray is effective in detecting internal lesions and foreign bodies, and aids in victim identification. However, this technique has limitations in visualizing soft tissue and microscopic abnormalities, so it should be used as a complement to traditional autopsy. In conclusion, the use of X-ray in autopsy improves diagnostic efficiency and accuracy, but should be combined with other imaging techniques for more comprehensive results.